Knowledge, Attitude and Practice on Dengue among Adult Population in Felda Sungai Pancing Timur, Kuantan, Pahang - AA, Karimah Hanim; MR, Razman; AR, Jamalludin; EH, Nasreen; Phyu, Htike Myat; L, SweSwe; P, Hafizah (IIUM Medical Journal Malaysia, 2017)
Background: With increasing number of dengue cases in Malaysia, it’s of utmost importance that immediate action be taken to limit the epidemic. Since dengue control is a behavioral problem, the knowledge, attitude and practice in population needs to be studied in order to control the disease. Hence, the aim of this study is to assess knowledge, attitude and practice regarding dengue and its associated factors among adult residents of Felda Sungai Panching Timur (SPT), Kuantan, Pahang, 2014. Method: A cross sectional study was carried out involving 265 adult respondents. A face to face interview questionnaire which was divided into 2 parts (Part A: Sociodemoghraphic; Part B: Knowledge, Attitude and Practice) was used. Data was analyzed using descriptive statistics, simple and multiple logistic regression. Results: 53.2% of the respondents had good knowledge about dengue and it was found that the main source of information from mass media (76.6%). However, only 43.4% were found to have good attitude towards dengue. Multiple Logistic Regression analysis showed there was no association between sociodemographic characteristics with the level of knowledge and attitude towards dengue. There was also no association found between knowledge of dengue and the attitude of the respondents towards dengue. Descriptive analysis on the practice of dengue showed majority of the respondents who had possible breeding site for Aedes mosquitos (water container, drains/gutter roof/flower pots/tires) in their compound practiced good habit in preventing the Aedes mosquitoes from breed. Conclusion: Although knowledge and practice towards dengue is good, their attitude require improvement.